Implementing a university e-learning strategy: levers for change within academic schools - Rhona Sharpe; Greg Benfield; Richard Francis (Association for Learning Technology, 2006)
This paper describes the implementation of an e-learning strategy at a single higher education institution in terms of the levers used to promote effective uptake and ensure sustainable embedding. The focus of this work was at the level of the academic school using a range of change practices including the appointment of school-based learning technologists and e-learning champions, supporting schools to write their own strategies, a pedagogical framework of engaging with e-learning, and curriculum development and evaluation of school-supported projects. It is clear that the implementation of the e-learning strategy has led to a large and increasing proportion of our students experiencing blended learning. In addition, there are initial indications that this has enhanced some learning and teaching processes. Where there has been sustainable embedding of effective e-learning, the following levers were identified as particularly important: flexibility in practices that allow schools to contextualise their plans for change, the facilitation of communities of key staff and creating opportunities for staff to voice and challenge their beliefs about e-learning.